Aspergillus terreus (Trichocomaceae): A Natural, Eco-Friendly Mycoinsecticide for Control of Malaria, Filariasis, Dengue Vectors and Its Toxicity Assessment Against an Aquatic Model Organism Artemia nauplii - Ragavendran, C.; Srinivasan, R.; Kim, Myunghee; Natarajan, Devarajan (Frontiers in Pharmacology, 2018)
Vector-borne diseases like malaria, filariasis, and dengue are transmitted by mosquitoes and they cause global mortality and morbidity due to an increased resistance against commercial insecticides. The present study was aimed to evaluate the neurobehavioral toxicity, knock-down effect, histopathology, ovicidal, adulticidal, and smoke toxicity effect of Aspergillus terreus extract against three mosquito species, namely Anopheles stephensi, Culex quinquefasciatus, and Aedes aegypti (Diptera: Culicidae). The isolated fungal strain was identified as A. terreus (GenBank accession no: KX694148.1) through morphological and molecular (phylogenetic) analysis. The morphological changes in the treated fourth instar larvae shown the demelanization of cuticle and shrinkage of the internal cuticle of anal papillae. The time duration of extract exposure against the larvae determines the level of toxicity. The extract treated larvae were displayed excitation, violent vertical and horizontal movements with aggressive anal biting behavior as the toxic effect on the neuromuscular system. The results of the biochemical analysis indicated that a decrease in the level of acetylcholinesterase, α-carboxylesterase, and β-carboxylesterase in extract treated fourth instar larvae of all tested mosquito species. The findings of histopathological investigation shown the disorganization of the abdominal region, mainly in mid, hindgut, and gastric caeca, loss of antenna, lateral hair, caudal hair, upper and lower head hairs in the mycelium extract treated An. stephensi, Cx. quinquefasciatus, and Ae. aegypti. The ovicidal bioassay test results showed the mosquito hatchability percentage was directly related to the concentrations of mycelium extract. Nil hatchability of mosquito eggs was noticed at 500 μg/ml concentration. The adulticidal activity of fungal mycelia ethyl acetate extract resulted in a dose-dependent activity (15 and 30 min recovery periods). The higher concentration of extract (1000 mg/L) acted as a repellent, the adult mosquitoes showed restless movement, uncontrolled/anesthetic flight at last died. The better adulticidal activity was observed in the ethyl acetate extract against An. stephensi, Cx. quinquefasciatus followed by Ae. aegypti with the best score of LD50 and LD90 values and nil mortality was found in the control. The results of smoke toxicity assay of the mycelia extract exhibited significant mortality rate against Ae. aegypti (91%), Cx. quinquefasciatus (89%), and An. stephensi (84%). In addition, the present investigation reported the stability and toxic effects of A. terreus mycelium ethyl acetate extract on Artemia nauplii. The swimming speed (0.88 mm s-1) of A. terreus was reduced with ethyl extract 24 h treatment whereas, the control A. nauplii showed the normal speed of 2.96 mm s-1. Altered behavior and swimming movement were observed in the 8 h A. terreus mycelium extract treated A. nauplii. A pale yellow color substance (metabolites) was found in the mid-gut region of the mycelial extract exposed A. nauplii. The outcome of the present study, suggest that the A. terreus metabolites might serve as an alternative, cost-effective, eco-friendly, and target specific mosquitocidal agent in the future.